Management - Robbins, Stephen P.; Coulter, Mary (Boston, Massachusetts : Prentice-Hall, 2012)
This course and this book are about management and managers.
The world of management -- Managing in the twenty-first century -- Planning -- Organizing -- Leading -- Controlling
Includes index.
Keywords: MANAGEMENT